Personal Reflections on U.S. Federal Foresight Initiatives in the 1970s. (September 2019) - Hunter, Kenneth W.
During the 1970s, the planning and foresight community in the United States worked very hard to incorporate the long view—foresight perspectives and practices—into governmental functions when and where ever we could, especially in that decade's major legislative accomplishments. Following is a brief outline of initiatives I had the pleasure of working on. While most of these activities were ended over the following generation, they show what can be accomplished with visionary leadership when the time is right.